PENINGKATAN KEMAMPUAN KOGNITIF SISWA MELALUI METODE BUZZ GROUP DAN IMPLEMENTASI MULTIMEDIA BERBASIS GOOGLE EARTH DALAM PEMBELAJARAN SEJARAH DI SMAN 1 TINAMBUNG - Nur Fadia; Patahuddin Patahuddin; Bahri Bahri; Ahmadin Ahmadin; Najamuddin Najamuddin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
This research aims to determine the increase in cognitive abilities of Class XI IPS students at SMAN 1 Tinambung through the application of buzz group and Google Earth-based multimedia methods in learning history. This type of research is classroom action research (PTK) with research subjects being students of Class XI IPS SMAN 1 Tinambung. The data collection techniques used are observation, interviews, tests and documentation. The data validation technique uses member check. The results of the research show that: 1) Increasing students' cognitive abilities through the active knowledge sharing method and implementing Google Earth-based multimedia in history learning at SMAN 1 Tinambung in cycle I shows that students experienced very good cognitive ability development (SB) percentage of 25% or value the average is 88.5 and the good category (B) is 37.5% or the average value is 81.22. Meanwhile, students in the sufficient category (C) had 25% or an average score of 70.83 and students in the poor category (K) had 12.5% or an average score of 64.67. So the average result of observation of the development of cognitive abilities for class XI IPS was 78.37 in cycle I. 2) In cycle II, almost all students experienced very good cognitive ability development (SB) with a percentage of 54.16% or an average score of 91.38 and a good category (B) of 37.5% or an average score of 84 and students sufficient category (C) 8.33% or average value 74.5. So it was obtained that the average observation result of the development of cognitive abilities in class XI IPS increased in cycle II, namely 87.20. 3) The use of buzz group multimedia methods based on Google Earth as a learning medium for material on the entry of European nations into the archipelago has increased at every stage. The total test scores from a score of 1,784 (pre cycle) increased by 97 scores to 1,881 (cycle I) and in post cycle II increased by 212 scores to 2,093 (cycle I). The lowest score in one class also increased from a score of 62 (pre cycle) to 64 (cycle I) and 76 (cycle II), while the highest score also increased, namely from 87 (pre cycle) to 90 (cycle I) and 96 (cycle II).